Diseño e implementación de una tarjeta de adquisición de datos para el análisis en línea de fallas en el rotor y rodamientos en un motor de inducción trifásico (2022)
Industrial processes within companies are a fundamental part of carrying out operations in a continuous and orderly manner. It is necessary to constantly monitor each machine through reliable techniques through H/ W (Hardware-Software) devices, which can anticipate possible inconveniences within them for the development of operations. There are several monitoring techniques for induction machines. Among the most used techniques for the process are: MCSA (Motor Current Signature Analysis), EPVA (Extended Park's Vector Approach) and ESA (Electric Power Spectral Analysis). These analyze through the consumption of current and voltage in frequency domain, giving the behavior of the state of the machine at work. In the present final project, 3 of the monitoring techniques mentioned above are used to detect failures on broken bars in the squirrel cage type rotor and bearings, through the frequency analysis of the behavior of the motor, for this reason two mathematical tools are used, Park and fast Fourier transformation to obtain the necessary analyzes in the analyzed motor classification state Finally, the design, construction, and implementation of a data acquisition card capable of detecting these failures was carried out, showing analysis and test results implemented with the motors available in the electronics laboratory of the Guayacanes building of the Pontificia Universidad Javeriana Cali, resulting in a functional prototype capable of performing an online analysis to detect failures of the broken bars in the squirrel cage type rotor and bearings. As a final product, a prototype that takes the information from the monitoring of the electrical variables of the machine, processes and displays the results of the status of the rotor bars and bearings on the LCD screen of the data acquisition card and by means of a communication protocol through the Ethernet port is delivered. The visualization of the results of the indicators of broken rotor bars and bearings is achieved on the developed website, obtaining an average of system effectiveness of 95% for the detection of broken rotor bars and 60% for bearings.